Legal Position on The Concept of Civil Relations with Respect to Out of Wedding Children - Novi, Merry Marcella; Usman, Rachmadi; Nurunnisa (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
Analyzing the position or legal status of illegitimate children from a Civil Law perspective and analyzing whether or not illegitimate children have the right to inherit from their biological father. Theoretically, the results of this research can be useful and contribute ideas to society in understanding what is meant by the relationship with the legal position of illegitimate children in the concept of civil law. Practically, it can provide input for legal practitioners so that it can be used as a basis for thinking in terms of the legal position of illegitimate children in the concept of civil law. The first research result obtained is to know the position of illegitimate children in a civil law perspective which is divided into 2 (two), namely children who are born out of wedlock, but can be recognized in an authentic way and children who are born out of wedlock but cannot be recognized. The second research result is that illegitimate children who have received recognition from their biological father have the right to inherit from their biological father based on Constitutional Court Decision Number 46/PUU-VIII/2010 which decides that Article 43 Paragraph (1) of the Marriage Law which must then be read with